Gender and Social Inclusion in NDC Planning and Implementation in Africa: Livestock and Climate Smart Agriculture - Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
A review of NDC planning and implementation documents, strategies and action plans for Africa since 2020 found that women and youth are increasingly recognized as users or managers of livestock or climate-smart agriculture (CSA). Of 54 countries, 21 integrate gender into livestock planning and implementation, and 21 integrate women and youth into NDC planning and implementation for CSA.